Penerapan Program Literasi Sains Untuk Meningkatkan Keterampilan Berfikir Ilmiah Siswa di TK Nurul Illmi Sumbawa - Suryanti; Syahru Ramadhan; Hermansyah; Anwar Sadat (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
The background of the problem underlying this research is the students' low understanding of basic scientific concepts such as the introduction of nature, animals, plants and the surrounding environment. This can be seen from the results of initial observations that show a gap in the ability to recognize, read, and write related to the world of science. This type of research is descriptive research with a qualitative approach. The data collection techniques used include observation, interviews, and documentation. The main data sources came from students, teachers, and observations of learning activities carried out at Nurul Illmi Kindergarten. Data analysis techniques were carried out inductively, by identifying patterns in the data obtained to draw conclusions related to the impact of the application of science literacy. The results showed a significant increase in students' scientific thinking skills after the science literacy program was implemented. Out of 30 students, 22 students showed good progress, 5 students were in the moderate category, and 3 students were still in the deficient category. This indicates that the program is effective in improving children's understanding and scientific thinking skills. As a follow-up, this study serves as a reference for researchers and teachers to look more carefully at science literacy programs as a fundamental need for children in learning.